(untitled) (LACCEI, 2024)
This research aims to analyze the transient dynamic behavior of beams using the Timoshenko theory. The proposed formulation employs three independent variables for the displacement field to apply them on Hamilton’s Principle. Temporal approximation is developed through Newmark method. The validity of this approach is given by numerical results obtained for cantilever and simply supported beams from comparing to similar researches.